Analisis Wacana Kritis Van Dijk Pada Teks Berita Online Kasus Pembunuhan Serta Pemerkosaan Vina Dan Kekasihnya Pada Media Liputan6.Com - Luci E Banjarnahor; Nur Annisa F; Novita Yulianti; Yolanda G Purba; Depiska T Simamora; Mustika Wati Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to focus on the analysis of Teun A. Van Dijk's critical discourse model in online news texts which discuss the murder and rape case of Vina and her lover published by Media Liputan6.com. In this analysis, Van Dijk's model which includes three main dimensions, namely text, social cognition and context, is used to understand how online news discourse describes and manifests these events. The research results show that critical discourse analysis can help in revealing how online news discourse influences and is influenced by ideology, knowledge and interests related to the event. Thus, this analysis can contribute to a deeper understanding of how news discourse can influence and be influenced by the social and ideological context associated with the event.